The Relationship Between Resilience and Mental Health in Chinese College Students: A Longitudinal Cross-Lagged Analysis - Wu, Yin; Sang, Zhi-qin; Zhang, Xiao-Chi; Margraf, Jürgen (Frontiers in Psychology, 2020)
The relationship between resilience and mental health was examined in three phases over four years in a sample of 314 college students in China. We used the Depression Anxiety Stress, the Positive Mental Health, and the Resilience Scales. Results revealed that first-year students and senior year students experienced higher negative mental health levels and lower positive mental health levels than junior year students. Cross-lagged structural equation modeling analyses showed that resilience could significantly predict mental health status in the short term, namely within one year from junior to senior year. However, the predicting function of resilience for mental health is not significant in the long term, namely within two years from freshman to junior year. Additionally, the significant predicting function of individuals’ mental health for resilience is fully verified for both the short and long term. These results indicate that college mental health education and interventions could be tailored based on students’ year in college.